ANALISIS HUBUNGAN AUDITOR-KLIEN : FAKTOR-FAKTOR YANG MEMPENGARUHI AUDITOR SWITCHING - Silvya Ayu Putri Pradita; Herry Laksito (Diponegoro Journal of Accounting, 2015)
The financial statements are the responsibility of the form to the principal agent in accordance with agency theory. To avoid the presence of information asymmetry between the two sides, a solution that can be traveled is doing an engagement with the auditor. A long period of the audit tenure between the auditor and the client has an impact on auditor independence. One suggestion to remain independent is the auditor rotation . Past research on auditor switching showed different results. The purpose of this study is to examine the factors that affect the auditor switching using empirical studies on companies listed in Indonesia Stock Exchange in 2011-2013.This study used secondary data from the financial statements of 30 companies manufacturing in Indonesia Stock Exchange website during 2011-2013. Data were analyzed using logistic regression with the company's financial condition, audit opinion and the client size audit opinion as independent variables, as well as switching auditors as the dependent variable.The test results of the research hypothesis indicates that the audit opinion negatively affect the auditor switching. While the company's financial condition and client size does not significantly affect the auditor switching.